2016
DOI: 10.1007/s12243-016-0510-2
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the usability of electronic voting systems for complex elections

Abstract: Many studies on electronic voting evaluate their usability in the context of simple elections. Complex elections, which take place in many European countries, also merit attention. The complexity of the voting process, as well as that of the tallying and verification of the ballots, makes usability even more crucial in this context. Complex elections, both paper-based and electronic, challenge voters and electoral officials to an unusual extent. In this work we present two studies of an electronic voting syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…While the results of some studies revealed high satisfaction scores, they did not measure verification effectiveness in terms of the extent to which the participants were actually able to verify their votes. The evaluation of effectiveness was included in other studies, such as Pret-a-Voter and Scantegrity II [1,2], BingoVote [5], StarVote [3] and EasyVote [8]. While some of these studies report high rates of success in terms of verifications [3,8], the results of other studies [1, 2, 5] reveal several issues.…”
Section: Previous Studies On Human Factors In Verifiable E-voting Sysmentioning
confidence: 99%
See 2 more Smart Citations
“…While the results of some studies revealed high satisfaction scores, they did not measure verification effectiveness in terms of the extent to which the participants were actually able to verify their votes. The evaluation of effectiveness was included in other studies, such as Pret-a-Voter and Scantegrity II [1,2], BingoVote [5], StarVote [3] and EasyVote [8]. While some of these studies report high rates of success in terms of verifications [3,8], the results of other studies [1, 2, 5] reveal several issues.…”
Section: Previous Studies On Human Factors In Verifiable E-voting Sysmentioning
confidence: 99%
“…The evaluation of effectiveness was included in other studies, such as Pret-a-Voter and Scantegrity II [1,2], BingoVote [5], StarVote [3] and EasyVote [8]. While some of these studies report high rates of success in terms of verifications [3,8], the results of other studies [1, 2, 5] reveal several issues. These include misconceptions related to the verification process, leading to study participants being unable to complete the verification successfully.…”
Section: Previous Studies On Human Factors In Verifiable E-voting Sysmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evaluations include investigations into the usability of paper ballots, paper punch cards and lever machines [14,20,26]. Further studies [7,13,16,21,29,48] have focused on the usability of Direct Recording Electronics (DREs), the computers used for voting in polling stations. Smartphone-based systems have also been investigated [15].…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, building blocks of private and untraceable communication services could potentially also be reused in other privacy-critical applications that are currently under active research, such as electronic voting systems [BV14] or privacy-preserving location-based services [MCA06,HCE11,DSZ14].…”
Section: Introductionmentioning
confidence: 99%